PENGARUH KNOWLEDGE SHARING, DUKUNGAN ORGANISASI TERHADAP PERILAKU KERJA INOVATIF DENGAN KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI VARIABEL MODERASI - Meidawati, Devi; Subyantoro, Arief; Hikmah, Khoirul (UIN Sunan Kalijaga, 2023)
This study identifies the effect of knowledge sharing organizational support on the innovative work behavior of FDK UIN Sunan Kalijaga Yogyakarta lecturers moderated by transformational leadership. This research uses a quantitative approach, with a sample of 85 lecturers of FDK UIN Sunan Kalijaga Yogyakarta, using simple random sampling technique and distribution is online and offline, data analysis using SEM with Smart-PLS 4.0 software. The results show that (1) knowledge sharing has no effect on innovative work behavior, (2) organizational support affects innovative work behavior, (3) knowledge sharing has no effect on innovative work behavior moderated by transformational leadership, and (4) organizational support has no effect on innovative work behavior moderated by transformational leadership. This study explores innovative work behavior, which is the individual actions of lecturers who are able to support organizational management innovation. In achieving this innovation, knowledge sharing activities, organizational support, and the role of leaders needed. When the application of these things is high, it can increase the innovative work behavior of lecturers. But in reality, the knowledge sharing activities of FDK UIN Sunan Kalijaga Yogyakarta lecturers are still low, so the existing innovative work behavior is still lacking. Leaders also pay less attention to the welfare of lecturers fairly, so lecturers are less eager to make reforms.